Population mortality in advanced melanoma patients with and without response and progression; data from the Dutch Melanoma Treatment Registry. (March 2023) - van Breeschoten, Jesper; van den Eertwegh, Alfons J.M.; Hilarius, Doranne L.; Haanen, John B.; Blank, Christian U.; Aarts, Maureen J.B.; van den Berkmortel, Franchette W.P.J.; de Groot, Jan Willem B.; Hospers, Geke A.P.; Kapiteijn, Ellen; Piersma, Djura; van Rijn, Rozemarijn S.; et al.
Abstract: Introduction: When analysing patient survival, one is often interested in cause of death. Little is known about the presence of population mortality in advanced melanoma patients. The aim of this study was to assess population mortality after different response states in advanced melanoma patients in the Netherlands, and analyse the contribution of disease and population mortality for different age groups. Methods: We selected patients diagnosed between 2013 and 2019 with unresectable IIIC or stage IV melanoma, registered in the Dutch Melanoma Treatment Registry. A multi-state model with response states integrating population mortality was fitted. One-year landmark analyses were performed to assess outcomes after each response state. Results: Overall, 5119 patients were selected. Five-year probabilities of melanoma-related mortality in patients alive in complete response at one year after diagnosis increased with age, and was 17.2% (95% confidence interval: 13.0–21.4) for patients aged <65 years and 28.7% (95% confidence interval: 24.3–33.1) in patients aged ≥80 years. Population mortality only played a large role for older patients (75 years and above) alive at 1 year after diagnosis with a partial or complete response. Conclusion: Even though survival outcomes of advanced melanoma patients have improved over the last decade, the vast majority of patients still die due to melanoma-related mortality. Highlights: Melanoma-related mortality after tumour responses has not been studied so far. Using multi-state models, the prognostic impact of response states was assessed. Melanoma-related mortality dominates population mortality in advanced melanoma. Population mortality plays a role in patients ≥75 years who respond to therapy.